2008
DOI: 10.1007/s11355-008-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

How management practices affect arthropod communities on Japanese golf courses?

Abstract: Potentially, golf courses could act as wildlife refuges under adequate golf course management. We assessed the impacts of golf course managements on arthropod communities by analyzing arthropod community data. Arthropods were collected using a sweeping-net method from turf areas. Information of management applied in each golf course such as frequency of chemical use, length of grass was obtained by field measurements and also from interviews based on management records with green keepers. In total, 92 inverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Smitley et al (1998) also found greater diversity in ground-dwelling predatory beetles in golf rough (tall grass) regions than in green (shorter grass). Delphacids on golf courses in Japan were abundant and most common in longer grass (Yasuda et al 2008). Mowing frequency varied from lawn to lawn and also might have affected the arthropod abundance in turfgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Smitley et al (1998) also found greater diversity in ground-dwelling predatory beetles in golf rough (tall grass) regions than in green (shorter grass). Delphacids on golf courses in Japan were abundant and most common in longer grass (Yasuda et al 2008). Mowing frequency varied from lawn to lawn and also might have affected the arthropod abundance in turfgrass.…”
Section: Discussionmentioning
confidence: 99%
“…When such an adaptive cycle continues, pest resistance and pesticide usage increase continuously, which may aggravate the burden on the environment. The Chiba prefecture established a 'Regulation of Golf Course Development Plans in Chiba' in 1994, which prohibits the use of any chemicals to control weeds and pests on golf courses constructed after 1994 [40,41]. It also regulates the amounts of pesticides that can be used on golf courses built before 1994.…”
Section: Optimal Management Plan For Pesticide Usage On Golf Coursesmentioning
confidence: 99%
“…Golf courses can provide suitable habitat for various types of wildlife, such as birds, frogs, and insects (Tanner & Gange, ; Yasuda & Koike, ; Yasuda et al ., ; Saarikivi et al ., ). Golf courses, when constructed from monocultural agricultural fields, may increase small‐scale habitat heterogeneity, and thus host high species richness (Colding & Folke, ).…”
Section: Introductionmentioning
confidence: 98%
“…Debate whether golf courses are seen as ‘green deserts’ or as ‘key sanctuaries for wildlife’ has been ongoing for the past decade with highly polarised opinions and little scientific data to support the findings. Until recently (Tanner & Gange, ; Yasuda & Koike, ; Yasuda et al ., ), however, the effects of golf course development on the biota of the course area have not been thoroughly studied. Such studies are important since up to 70% of an average 18‐hole golf course is considered rough or out‐of‐play areas that could be managed for the benefit of wildlife (Tanner & Gange, ).…”
Section: Introductionmentioning
confidence: 99%